A xyloglucan endotransglucosylase/hydrolase gene, IbXTH16, increases cold tolerance in transgenic sweetpotato - Yu, Tao; Pan, Jiaquan; Liu, Sitong; Yang, Zitong; Liu, Zhenlei (Frontiers in Genetics, 2025)
IntroductionLow temperature is a key environmental factor that threaten sweetpotato growth and development. In-depth studies on the gene functions underlying cold resistance are important for genetic engineering in sweetpotato.MethodsThe IbXTH16 gene was cloned using a homologous cloning approach. Its expression was detected in sweetpotato leaves subjected to low-temperature stress and brassinosteroid treatment. Subsequently, the IbXTH16 gene was introduced into sweetpotato variety Lizixiang to generate IbXTH16-overexpressing plants, thereby enabling the functional validation of the IbXTH16.Results and discussionThe IbXTH16 gene was cloned from the cold-tolerant variety LHS21. Its 879 bp coding sequence encoded a 292 aa protein with a molecular weight of 32.983 kDa and a pI of 8.47. The 2039 bp genomic sequence of IbXTH16 contained two exons and one intron. The IbXTH16 protein was localized in the cell membrane. IbXTH16 was strongly induced by 4°C and brassinosteroid. IbXTH16 positively regulates cold tolerance of sweetpotato by activating the BR and proline pathways.